pH-Responsive DNA Motif: From Rational Design to Analytical Applications - Zheng, Lin Lin; Li, Jin Ze; Li, Ying Xu; Gao, Jian Bang; Dong, Jiang Xue; Gao, Zhong Feng (Frontiers in Chemistry, 2021)
pH-Responsive DNA motif have attracted substantial attention attributed to its high designability and versatility of DNA chemistry. Such DNA motif typically exploit DNA secondary structures that exhibit pH response properties because of the presence of specific protonation sites. In this review, we briefly summarized second structure-based pH-responsive DNA motif, including triplex, i-motif and A-C mismatch base pair-based DNA devices. Finally, remaining challenge and prospect of pH-responsive DNA motif are also discussed.